(3GdLGeY Hjf GdYde hGdYed hGdfGaY aj WGYI GdMjds - (3HOjY GdReGf CHh GdYR CHh HcQ ESeGYjd Hf GdQRGQ GdLRQj, GHf GdQRGR GdLRQj,J (B602 (3g` s
(3ChdgG (B:s
(3aEfi JUaMJ cJH GdeJbOejf hCYeGd GdeJCNQjf CSHGH GdMjd ai GdMQcGJ GdeTHgI HGdQhMGfjI hBdGJ GdeGA hHGTQJ YdGL gPg GdUfGYI hCdaJ gPG GdcJGH jSJcd Ydi HYV hCTcGd GNJQYJgG hde CYde Cfi SHbJ EdjgG s
(3BNQgG (B:s
(3hGdMeO ddg hMOg hUdi Gddg Ydi eMeO hBdg s
(3HgG CTcGd JhVjMjIs
(3YdjgG eWGdYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B364s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
Keywords: (3GdQjGVjGJs